Autogenous shrinkage prediction models and microstructure of UHPC with single or binary addition of an expansive agent and steel fibers - Weng, JiaRui; Liao, WenCheng (Frontiers in Materials, 2024)
The low water/binder ratio of ultra-high performance concrete (UHPC) often results in its high autogenous shrinkage. Our study explored the effect of the single or binary addition of a CaO-based expansive agent (CEA) and steel fibers on flowability, compressive strength, flexural strength, microstructure, and autogenous shrinkage of UHPC. X-ray diffraction (XRD), thermogravimetric (TG) analysis, scanning electron microscopy (SEM), and mercury intrusion porosimetry (MIP) were applied to reveal the effects of CEA and steel fibers on hydration products and microstructure characteristics of UHPC. Experimental results show that the autogenous shrinkage of UHPC decreased markedly with the single or binary addition of CEA and steel fibers. Relative to the control group, autogenous shrinkage of UHPC with 2.5% dosage of single steel fibers, 6% dosage of single CEA, and binary addition of 2.5% steel fibers and 6% CEA decreased 17.8%, 10.9%, and 30.8% at 180 days, respectively. Steel fibers could enhance the mechanical performance of UHPC; nevertheless, they would decrease the flowability of UHPC. Meanwhile, the addition of CEA in the UHPC mixture not only maintained the mechanical properties and flowability but also decreased the autogenous shrinkage. Diffraction peak intensity and endothermic peak of Ca(OH)2 and the pore volume of 10–50 nm diminished with the content of CEA; however, that of C-S-H gel and ettringite increased. The prediction accuracy of nine shrinkage models (FHWA model, Lee model, Yoo model, JSCE model, B4 model, JonassonH model, Eurocode 2 model, CEB model, and DilgerW model) is analyzed with RE, Rnew2, and autogenous shrinkage of UHPC in this paper.